Integrated methodology for the prediction of helicopter rotor noise at mission level - Vouros, Stavros; Goulos, Ioannis; Pachidis, Vassilios (Elsevier, 2019)
This paper presents an integrated approach for the aeroacoustic assessment of fourdimensional rotorcraft operations. A comprehensive rotorcraft code is utilized to model aircraft flight dynamics across complete missions. A free-wake aero-elastic rotor model is employed to predict high-resolution unsteady airloads, including blade-vortex interactions, at each mission element. A rotor aeroacoustics code is developed to calculate source noise and far-field ground acoustic impact. Time-domain acoustic formulations are used to evaluate near-field noise generation across designated acoustic spherical surfaces surrounding the helicopter main rotor. A numerical procedure is developed for the derivation of acoustic spheres on-the-fly, coupled with trajectory-adaptive ground observer grids. The individual analytical models are incorporated into a mission analysis numerical procedure. The applicability of the integrated method on “real-world” rotorcraft operations is demonstrated for two generic, four-dimensional missions, without the need of pre-stored noise data. The proposed approach provides insight into helicopter noise prediction at mission level, elaborating on the coupling of aeroelastic rotor response with rotorcraft flight dynamics and aeroacoustics.
Keywords: Computational aeroacoustics; Helicopter noise prediction; Mission analysis; Acoustic spheres; Ground noise footprint